Sticking your neck out and burying the hatchet: what idioms reveal about embodied simulation - Kacinik, Natalie A. (Frontiers in Human Neuroscience, 2014)
Idioms are used in conventional language twice as frequently as metaphors, but most research, particularly recent work on embodiment has focused on the latter. However, idioms have the potential to significantly deepen our understanding of embodiment because their meanings cannot be derived from their component words. To determine whether sensorimotor states could activate idiomatic meaning, participants were instructed to engage in postures/actions reflecting various idioms (e.g., sticking your neck out) relative to non-idiomatic control postures/actions while reading and responding to statements designed to assess idiomatic meaning. The results showed that statements were generally more strongly endorsed after idiom embodiment than control conditions, indicating that the meaning of idiomatic expressions may not be as disconnected from perceptual and motor experiences than previously thought. These findings are discussed in terms of the mirror neuron system and the necessity of pluralistic contributions from both sensorimotor and amodal linguistic systems to fully account for the representation and processing of idioms and other figurative expressions.